The relationship between corporate governance and firm performance: Moderating role of corporate social responsibility - Miao Wenhao (2020)
Under the complex and changeable global market in the 21 st century, continuous performance is a key driver of a firm especially in coping with a growing number of challenges arising from unforeseen events in business landscape. As a matter of fact, the rapid growth in capital market in Asia especially China has brought the importance of the corporate governance in portraying firm's future performance. More importantly, combined the in-depth development of economic globalization with the Chinese rapid economic development, Corporate Social Responsibility (CSR) has attracted great attention in China. Given the importance of both corporate governance and CSR, this study examined the moderating role of CSR on the relationship between corporate governance and firm performance based on Listed firms in China. To examine their relationship, this study employed panel data regression techniques using stock data to represent the aggregate composition of the Shanghai Stock Exchange 180 Index (SSE 180 index) from 2010 to 2019. All the data collected from database were analyzed through E-VIEWS and STATA software. After controlling the possible endogeneity problems and robustness check, the empirical results are as follows: board size, CEO duality and CEO compensation could improve firm performance. There is a significant negative relationship between debt and firm performance. CSR could moderate (reduce) the positive relationship between board independence and firm performance as well as the positive relationship between CEO compensation and firm performance. In conclusion, the result showed that not all so-called good corporate governance can produce better firm performance based on unique Chinese capital market and although CSR is considered as a useful business strategy, it still has a lot of room for improvement in China. Therefore, companies should constantly improve corporate governance structure and CSR level to achieve the purpose of improving firm performance.